A short history of thrombectomy – Procedure and success analysis of different endovascular stroke treatment techniques. Issue 2 (April 2021) - Friedrich, B; Boeckh-Behrens, T; Krüssmann, V; Mönch, S; Kirschke, J; Kreiser, K; Berndt, M; Lehm, M; Wunderlich, S; Zimmer, C; Kaesmacher, J; Maegerlein, C
Background: The historical development of interventional stroke treatment shows a wide variation of different techniques and materials used. Thus, the question of the present work is whether the technical and procedural differences of thrombectomy techniques lead to different technical and clinical results. Methods and results: Analysis of a mixed retrospective/prospective database of all endovascular treated patients with an occlusion of the Carotid-T or M1 segment of the MCA at a single comprehensive stroke center since 2008. Patients were classified regarding the technical approach used. Six hundred sixty-eight patients were available for the final analysis. Reperfusion rates ranged between 56% and 100% depending on the technical approach. The use of balloon guide catheters and most recently the establishment of combination techniques using balloon guide catheters, aspiration catheters and stent retrievers have shown a further significant increase in the rates of successful recanalization, full recanalization and first-pass recanalization. Additionally, the technical development of interventional techniques has led to a subsequent drop in complications, embolization into previously unaffected territories in particular. Conclusion: Technical success of MT has improved substantially over the past decade owing to improved materials and procedural innovations. Combination techniques including flow modulation have emerged to be the most effective approach and should be considered as a standard of care. Level of evidence: Level 3, retrospective study.